Genetic Profile Assessment of Giant Clam Genus Tridacna as a Basis for Resource Management at Wakatobi National Park Waters - Muhammad Nur Findra; Isdradjad Setyobudiandi; Nurlisa Alias Butet; Dedy Duryadi Solihin (Marine Science Department Diponegoro University, 2017)
Giant clam population has been decreased in a few years. Resource management requires information from various aspects, such as ecological, population, and other aspects. This study was aimed at assessing the genetic profile of Tridacna giant clam in Wakatobi National Park waters using Cytochrome oxidase subunit I (COI) genetic marker. Sample collection was conducted around the three main islands, i.e., Wangi-wangi, Kaledupa, and Tomia. Genetic analysis using COI gene may contribute in identifying giant clams up to the species level and showed the relationship among species. The research found 41 specific nucleotide sites for the clams. T. crocea, T. squamosa and T. maxima had 2, 15 and 24 sites, respectively. COI gene as a biological marker was able to separate groups of giant clam by species. Nucleotide variation of T. crocea from Wakatobi was the highest among other locations, so it could be used as a genetic source for translocation and domestication. Keywords: cytochrome oxidase subunit I, specific nucleotide, Tridacna, Wakatobi National Park